A Transatlantic history of public administration Analyzing the USA, Germany, and France - Sager, Fritz; Rosser, Christian; Mavrot, Celine; Hurni, Pascal Y. (Edward Elgar, 2018)
Offering a thorough analysis of the transatlantic history of Public Administration, the conclusion argues that it is vital to learn from the past, in order to make Public Administration more realistic in theory, as well as more successful in practice.